From photos to realistic video games, in the blink of an eye.
Companies willing to stand out in today's video game industry need three core assets : an original concept and scenario, an intuitive gameplay and photo-realistic game environments. As vibrant as it may be, the European video game industry is caught up in this race, and small companies can hardly win without tremendous budgets being invested in their 3D environments. Technology developed under the CR-PLAY project-which enables the creation of realistic gaming environments based on photos and videos-may increase their chances.